Implementasi Kebijakan Forum Kewaspadaan Dini Masyarakat (FKDM) Dalam Mencegah Konflik Sosial Di Kota Surabaya - Nurmawati, Diyah (Innovative: Journal Of Social Science Research, 2025)
The main objective of this study was to explore the role of the Community Early Warning Forum (FKDM) in enhancing community engagement and communication with local government. This study emphasizes the importance of active interaction between FKDM members and government officials to build a strong network that facilitates the exchange of important information regarding potential threats to community safety. This engagement is essential to foster a sense of ownership and responsibility among community members towards their environment and safety. This study used a qualitative approach, focusing on the dynamics of communication during FKDM meetings. This study involved observing interactions between FKDM members and local government representatives, as well as collecting data on the types of information shared regarding community threats. This study also examined the roles of key figures in FKDM, such as the Chairperson and Vice Chairperson, in coordinating activities, collecting data, and formulating recommendations to the government. This method allows for a comprehensive understanding of the processes involved in community safety discussions and the effectiveness of the communication strategies used. The findings of the study indicate that FKDM plays a significant role in bridging the gap between the community and local government. Active dialogue during the meetings not only allowed for the exchange of information but also encouraged participation from all participants, resulting in a more accurate and comprehensive understanding of community issues. The study highlighted that despite the apparent peaceful environment, tensions and potential for conflict persist, necessitating proactive measures to address these challenges. The results underscore the effectiveness of FKDM in fostering open communication and collaboration, which are essential to maintaining community security and harmony.